FIELD BASED INSIGHTS INTO VERNACULAR OLIVE OIL PRODUCTION ON THE SYRIAN COAST (ROMAN–BYZANTINE PERIODS) - Maha Ismail (PEOPLE: International Journal of Social Sciences, 2026)
This paper examines how rural communities in the mountainous Syrian coastal hinterland adapted olive oil production technologies to rugged topography during the Roman and Byzantine periods. Based on the author’s field documentation (September 2023; October 2024) in villages including al-Jibliyyeh, Baʿbda, Dirmāneh, Dweir Baʿbda (al-Bayyāḍa), Falsaqo, and Harama (near Beit Yāshūṭ), the study analyzes rock-cut press installations characterized by basin morphology, gravity-assisted drainage, and limited or absent built superstructures. These design choices are interpreted as pragmatic responses to marginal landscapes and small- to medium-scale production needs, rather than indicators of technological inferiority. A comparative perspective with inland northern Syria (e.g., the Limestone Massif/“Dead Cities”) highlights a different investment pattern, where presses were more frequently integrated into architectural complexes and, in some cases, employed more elaborate mechanisms. The coastal corpus instead reflects decentralized production strategies shaped by terrain constraints, household or cooperative labor, and long-term reuse of stone-carved features. By integrating field observations with comparative archaeological and historical scholarship, the paper argues for rural technological resilience and agency in peripheral eastern Mediterranean contexts.